Keterlibatan Siswa (Student Engagement) sebagai Mediator Kompetensi Emosi dan Prestasi Akademik - I Wayan Dharmayana; - Masrun; Amitya Kumara; Yapsir G Wirawan (Jurnal Psikologi, 2012)
There is a hypothesis that emotional competencies have indirect effects to the academic achievement through school engagement and a higher Academic success requires higher emotional competencies and school engagement. This study aimed to test the hypothesis. It utilized subjects consisting of 417 excellent students. Psychological scale (emotional competence scale), Advanced Progressive Matrices (APM) intelligence test and documen-tations were used for collecting the data. A Structural equation modeling of AMOS 6.0 was applied to analyze the data. The important result of this study supported the hypothesis and affirmed that emotional competence indirectly affects the academic achievement through the school engagement. Based on the result of this research, it was suggested that the efforts and interventions have to include the aspects of emotional competence and school engagement as integral parts of educational program in the school. Keywords: emotional competence, student engagement, academic achievement